Integrating Digital Games Based Language Learning for EFL Speaking Skills Development: A Case Study in an Indonesian University - Sri Hariati Mustari; Nurdin Noni; Kisman Salija (Journal of English Culture, Language, Literature and Education, 2024)
Digital learning has become a potential learning tool since the COVID pandemic which causes the use of new technologies including digital games based language learning However the implementation still has challenges due to technical instructional and financial barriers Previous studies suggest exploring more teaching experiences related to the use of digital games based language learning for future contributions nbsp; This study aims to explore the implementation of digital games based language learning in higher education To achieve this goal this study was conducted in an Indonesian higher education the State University of Makassar by applying a qualitative case study to collect data The researcher collected the data from 2 lecturers recruited using a convenient sampling technique The thematic analysis was used to analyze the collected data nbsp; This study explores teacher experiences in using digital games based language learning in a speaking classroom This study found that the lecturers plan implement and evaluate digital games based language learning in three categories namely well moderate and low implemented From this result it is claimed academically that digital games based language learning DGBLL can be planned implemented and evaluated strategically in speaking classrooms based on learning objectives learning outcomes and students learning needs Combining technology with game based learning education can be more dynamic and relevant accommodating a variety of learning styles and motivating students to be more actively involved in the learning process < p>